Effect of Cement Shade and Light-curing Unit on Bond Strength of a Ceramic Cemented to Dentin - de Castro, Humberto Lago [UNESP]; Passos, Sheila Pestana [UNESP]; Zogheib, Lucas Villaca; Della Bona, Alvaro (Quintessence Publishing Co Inc, 2012)
Purpose: To evaluate the effect of cement shade, light-curing unit, and water storage on tensile bond strength (a) of a feldspathic ceramic resin bonded to dentin.Materials and Methods: The dentin surface of 40 molars was exposed and etched with 37% phosphoric acid, then an adhesive system was applied. Forty blocks of feldspathic ceramic (Vita VM7) were produced. The ceramic surface was etched with 10% hydrofluoric acid for 60 s, followed by the application of a silane agent and a dual-curing resin cement (Variolink II). Ceramic blocks were cemented to the treated dentin using either A3 or transparent (Tr) shade cement that was activated using either halogen or LED light for 40 s. All blocks were stored in 37 degrees C distilled water for 24 h before cutting to obtain non-trimmed bar-shaped specimens (adhesive area = 1 mm(2) +/- 0.1) for the microtensile bond strength test. The specimens were randomly grouped according to the storage time: no storage or stored for 150 days in 37 degrees C distilled water. Eight experimental groups were obtained (n = 30). The specimens were submitted to the tensile bond strength test using a universal testing machine at a crosshead speed of 1 mm/min. The data were statistically analyzed using ANOVA and Tukey's post-hoc tests (alpha = 0.05).Results: The mean bond strength values were significantly lower for the corresponding water stored groups, except for the specimens using A3 resin cement activated by halogen light. There was no significance difference in mean bond strength values among all groups after water storage.Conclusion: Water storage had a detrimental effect under most experimental conditions. For both cement shades investigated (Tr and A3) under the same storage condition, the light-curing units (QTH and LED) did not affect the mean microtensile bond strengths of resin-cemented ceramic to dentin.
Keywords: cement shade; ceramic; polymerization source; microtensile bond strength